Incorporating analytical hierarchy process and goal programming to design responsive and efficient supply chains. (2020) - Al-Husain, Raed; Khorramshahgol, Reza
Highlights: A holistic view of supply chain drivers is essential for a robust SC design. The contribution of each SC driver toward efficiency and responsiveness must be explicitly incorporated in the design process. To allow tradeoffs among the SC drivers and to assign weights to them will result in significant gains in both efficiency and responsiveness. A hybrid SC design is preferable since it attempts to simultaneously achieve efficiency and responsiveness. Abstract: The main aim of this article is to propose a new supply chain (SC) design methodology in order to enable organizations to better utilize their resources and structure their SC drivers to achieve the desired level of responsiveness and efficiency. A great challenge in this endeavor is that the SC drivers, which are categorized as logistical and cross-functional, are interrelated and have different (often conflicting) performance measures. By combining the analytical hierarchy process (AHP) with weighted binary goal programming (GP), this article introduces a two-stage approach to SC design. At the initial stage, the AHP model attempts to develop weights for the efficiency and responsiveness of the overall SC design as well as the individual SC drivers. These weights are subsequently used in the latter stage to construct a GP model to determine the optimal set of SC-driver decisions that would develop the overall satisfactory SC design.